Are we advancing universal health coverage through cataract services? Protocol for a scoping review. Issue 7 (8th July 2020) - Lee, Chan Ning; Ramke, Jacqueline; McCormick, Ian; Zhang, Justine H; Aghaji, Ada; Mwangi, Nyawira; Burn, Helen; Gordon, Iris; Yusufu, Mayinuer; He, Mingguang; Silva, Juan Carlos; Burton, Matthew J
Abstract : Introduction: Universal health coverage (UHC) includes the dimensions of equity in access, quality services that improve health and protection against financial hardship. Cataract continues to be the leading cause of blindness globally, despite cataract surgery being an efficacious intervention. The aim of this scoping review is to map the nature, extent and global distribution of data on cataract services for UHC in terms of equity, access, quality and financial protection. Methods and analysis: The search will be constructed by an Information Specialist and undertaken in MEDLINE, Embase and Global Health databases. We will include all published non-interventional primary research studies and systematic reviews that report a quantitative assessment of access, equity, quality or financial protection of cataract surgical services for adults at the subnational, national, regional or global level from population-based surveys or routinely collected health service data since 1 January 2000 and published through to February 2020. Screening and data charting will be undertaken using Covidence systematic review software. Titles and abstracts of identified studies will be screened by two authors independently. Full-text articles of potentially relevant studies will be obtained and reviewed independently by two authors against the inclusion criteria. Any discrepancies between the authors will be resolved by discussion, and with a third author as necessary. A data charting form will be developed and piloted on three studies by three authors and amendments made as necessary. Data will be extracted by two reviewers independently and summarised narratively and using maps. Ethics and dissemination: Ethical approval was not sought as the scoping review will only use published and publicly accessible data. The review will be published in an open access peer-reviewed journal. A summary of the results will be developed for website posting, stakeholder meetings and inclusion in the ongoing Lancet Global Health Commission on Global Eye Health.